Institutional transformation to engage a diverse student body - Thomas, Liz (Elizabeth); Tight, Malcolm (Bingley, U.K. : Emerald, 2011)
It is now widely accepted that institutional change is necessary to engage a diverse student body, both to encourage them to enter higher education (HE), and to enable them to be successful in HE. This book is premised on the need for institutional transformation: changing institutional structures, processes and governance; developing an inclusive culture and altering processes of knowledge creation (research) and knowledge transfer (learning and teaching). Key features of the book include: Developing the concept of institutional transformation and student engagement to widen participation in HE and improve student retention and success; Providing an analysis of how well institutions in England are doing in terms of taking a whole institution approach to widening participation, student diversity and success. Exploring the meaning of institutional transformation in relation to: outreach, admissions, induction and transition, learning and teaching, personal tutoring and support, research and progression beyond HE. Identifying approaches to managing institutional transformation. Involving students in the process of transformation. Illustrating and developing these themes through a serious of mini international case studies. The book aims to help readers engage with a number of the core higher education issues that have dominated UK and International policy over recent years.
ch. 1. Institutional transformation to engage a diverse student body / Liz Thomas -- ch. 1.1. Institutional transformation to engage a diverse student body at the Open University / Margaret Hart, Tony O'Shea-Poon -- ch. 1.2.'Resistance from the periphery?' : a case study of attempts to widen access to adult learners at a South African university / Salma Ismail, Linda Cooper -- ch. 2. Engaging students to improve retention and success / Liz Thomas -- ch. 2.1. From classroom resistance to school reform / Derek Bland -- ch. 2.2. Project 2013 : a model for increasing first-year at-risk student retention rates / Rashidah N. Andrews, Jayne K. Drake -- ch. 3. Institutional transformation to mainstream diversity / Liz Thomas -- ch. 3.1. Mainstreaming widening participation : institutional transformation from small beginnings / Amanda Ingleby -- ch. 3.2. Achieving a'fair go' at La Trobe University / Kerry Ferguson -- ch. 4. Mainstreaming widening access to engage students in higher education / Sue Hatt, James Tate -- ch. 4.1. The access tradition : widening participation and the University of Bedfordshire / Steve Kendall -- ch. 4.2. Access, aspiration and attainment : foundation studies at the University of South Australia / Christopher M. Klinger, Neil L. Murray -- ch. 4.3. Transferring from senior to higher vocational education in the Netherlands / Sabine Severiens, Rick Wolff, W{u3874}te Zijlstra -- ch. 5. Working together on widening access, admissions and transition into higher education / Janet Graham, Dan Shaffer -- ch. 5.1. Getting the higher education x-factor / Michelle Gammo-Felton -- ch. 5.2. Balancing mission and market in Chicago : an enrolment management perspective / Brian Spittle -- ch. 5.3. Acknowledgment of prior experiential learning to widen participation at the Universitlibre de Bruxelles : the challenge of the institutional message / Renaud Maes, Cile Sztalberg, Michel Sylin -- ch. 6. Transforming the learning experience to engage students / Kerri-Lee D. Krause -- ch. 6.1. Transforming the first year experience through learning communities / Scott E. Evenbeck, Frank E. Ross -- ch. 6.2. Inclusion and the student voice : lessons from the trinity inclusive curriculum strategy / Michelle Garvey -- ch. 6.3. Mainstreaming blended learning to enhance the access, learning and retention of students from equity groups / Violeta Vidaek-Hain, Blaenka Divjak, Renata Horvatek -- ch. 6.4. Defining identity, engaging teachers and engaging students :'education strengths' in a foreign branch campus / Glenda Crosling -- ch. 7. Engaging students to enhance progression beyond the first degree / Liz Thomas -- ch. 7.1. Transforming learning : engaging students with the business community / Sandra Hill -- ch. 8. Enabling institutional transformation to engage a diverse student body : necessary conditions and facilitating factors / Liz Thomas -- ch. 8.1. Establishing a'golden thread' : the path to ensuring institutional transformation / Jacqueline Stevenson -- ch. 8.2. Reversing frames : institutional development at Oslo University College / Marit Greek -- ch. 8.3. Developing an organisational culture where social justice and collaboration runs alongside widening participation / Vicky Duckworth -- ch. 8.4. Widening participation Bristol-fashion : embedding policy and practice at the Universities of Bristol and the West of England / Tony Hoare, Betsy Bowerman, Chris Croudace, Richard Waller.
Includes bibliographical references.
Keywords: Education, Higher -- Administration